DPSIR framework application supported by integrated watershed modeling for irrigation from Alqueva dam (Portugal) on Guadiana river estuary - Kebede, Shimeles Mulugeta (2011)
Dissertação de mest., Gestão da Água e da Costa, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2009